2019
DOI: 10.1111/jfpp.13922
|View full text |Cite
|
Sign up to set email alerts
|

Influence of germination on physicochemical, thermo‐pasting, and antioxidant properties of moong grain ( Vigna radiata )

Abstract: Moong grains (MG) were germinated for the different time period (1, 2, 3, 4, and 5 days) and the effect of germination time on the quality of MG flour was determined. A significant (p < 0.05) increase in nutritional composition, functional properties, and antioxidant activity of MG flour was observed upon germination. In comparison to control samples, increase in protein content (27.94–35.80 g/100g), the total color difference (15.56–22.18), total phenolic content (2.31–6.84 GAE/100g), and total flavonoid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
7
13
0
Order By: Relevance
“…Also, thermal alteration in the chemical structure of molecules associated with phenolic compound enhanced the TPC. The results of present study are comparable with the reported TPC for germinated moong (Sharanagat, Kumar et al, ), germination of oat seeds (Tian et al, ), roasted chickpea (Jogihalli, Singh, & Sharanagat, , microwave roasted chestnut (Wani et al, ), and roasted sorghum (Sharanagat, Suhag et al, ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Also, thermal alteration in the chemical structure of molecules associated with phenolic compound enhanced the TPC. The results of present study are comparable with the reported TPC for germinated moong (Sharanagat, Kumar et al, ), germination of oat seeds (Tian et al, ), roasted chickpea (Jogihalli, Singh, & Sharanagat, , microwave roasted chestnut (Wani et al, ), and roasted sorghum (Sharanagat, Suhag et al, ).…”
Section: Resultssupporting
confidence: 91%
“…The setback viscosity, which is related to the retrogradation of starch, also reduced drastically for roasted sample, indicating higher resistance of roasted starch to rearrangement and reorientation (Clifford, Chika, Jude, & Tochi, ). The trend of pasting properties of germinated BC flour is in agreement with the reported values of Jan et al () for germinated Chenopodium , Sharanagat, Kumar et al () for germinated moong, and Cornejo and Rosell () for germinated rice flour, whereas the pasting values for roasted BC flour are supported by Wani et al () for microwave roasted chestnut and Sharanagat, Suhag et al () for microwave roasted sorghum flour.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations